Pengaruh Media Konkret Terhadap Hasil Belajar IPA Pada Materi Wujud Benda Kelas V di Sekolah Dasar - Aina, Aina; Arni, Yusni; Fitriani, Fitriani; Febriantii, Devi (CV. PUSDIKRA MITRA JAYA, 2025)
Concrete media is media in the form of real objects that are around that are used to intermediaries to convey material to students. This study aims to determine the effect of science learning media on the material of changes in the form of objects in class V in elementary school. This research uses experimental research, the method used is Quasi experimental design with the type of posttest only control design. The sample used is cluster sampling in class V.A totaling 24 students and class V.C totaling 26 students. This study conducted a hypothesis test using the t test, namely the independent sample t-test in the experimental class and control class, namely the 2-tailed sig value obtained a value of 0.000 < 0.05, meaning that there is a significant value. Then for the value of tcount = 3.770 > ttable = 1.677 based on the hypothesis testing criteria if tcount > ttable then Ho is rejected and Ha is accepted. It can be Concluded that there is a significant effect of concrete media on science learning outcomes on the material of changes in the form of objects in class V in elementary schools.